LANDMARKS REGARDING THE EXTERNAL PUBLIC AUDIT IN ROMANIA - TRINCU-DRĂGUŞIN CRISTINA-PETRINA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2018)
This paper falls within the category of those about the external public audit in Romania and is intended to be an investigative approach through which we propose to bring in the light of the scientific reflectors certain significant landmarks in the field, starting from the premise that it is a subject of considerable interest from multiple directions. In the described context, the coordinates of the article focus on the topical elements of the approached field and include conceptual delimitations regarding the external public audit, normative approaches in our country, aspects regarding the organization, functioning and management of the supreme audit institution, the presentation of competencies, the field of application for the activities of the Romanian Court of Accounts, as well as its specific attributions related to the external public audit. At the end of the paper, the conclusions on the debated topic are outlined.